PERMOHONAN JASA INFRASTRUKTUR TEKNOLOGI INFORMASI DAN OPERASIONAL BERBASIS WEBSITE PADA PT.LAPI LABORATORIES - Ilamsyah Ilamsyah; Rosmawati Dwi; Dinny Kurnia Hermawan (UNIVERSITAS RAHARJA, 2018)
The increasing use of technology will increase the need for hardware as one of the support that is very important for the activities of a company. At PT. Laboratories currently have problems in making two way communication with the user so that required a structured system and realtime presntation of the data that can connect between thuse with the division of infrastructure and operations where the existing system is currently very less effective because it can not present activity data infrastructure division and operations in realtime against request made by the user, because the user request is only done orally and in the form of internal memo that is not terrecord which canbe forgotten anytime,lost or tucked and no output any request report made by the user. As for the data collection in this research is done by interview method, observation and literature study. The result of this research is in the wake of application system of information technology services especially the infrastructure and operational part which clear and structured from the beginning of application is made, progress until application is complete. Reports of progress workmanship and application can be printed.